End of life decisions in Malaysia: adequacies of ethical codes and developing legal standards - Jahn Kassim, Puteri Nemie; Alias, Fadhlina (Thomson Reuters, 2015)
End-of-life decision making is an area of medical practice in which ethical dilemmas and legal interventions have become increasingly prevalent. Decisions are no longer confined to clinical assessments, rather they involve wider considerations such as patient’s religious and cultural beliefs, financial constraints, and the wishes of family members. These decisions affect everyone concerned, including members of the community as a whole. Therefore, it is imperative that clear ethical codes and legal standards are developed to guide the medical profession on the best possible course of action for patients. This article considers the relevant ethical codes and legal provisions in Malaysia governing certain aspects of end-of-life decision-making. It highlights the lack of judicial decisions in this area as well as the limitations with the Malaysian regulatory system. The article recommends the development of comprehensive ethical codes and legal standards to guide end-of-life decision-making in Malaysia.